2003
DOI: 10.1136/aim.21.1-2.9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Electroacupuncture on Peripheral Nerve Regeneration in Rats

Abstract: This study was designed to examine the effects of electroacupuncture with direct current (DC) on peripheral nerve regeneration. The left sciatic nerve of 55 7-month-old rats was crushed at the thigh. They were ramdomly allocated to four groups: distal cathode DC group (n=15), distal anode DC group (n=14), sham operated group (n=13), and control group (n=13). In the distal cathode DC group, a cathode electrode was connected to an insulated acupuncture needle inserted at 1 cm distal to the injured site, while an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 19 publications
2
30
0
1
Order By: Relevance
“…Electro-acupuncture represents another method with minimal tissue damage and known to produce anti-hyperalgesia in animal models of inflammatory pain. Electro-acupuncture was also shown to improve motor recovery by assessing muscle electrical activity elicited under peripheral nerve stimulation [10]. However, no studies have explored its effects on peripheral nerve regeneration by measuring both motor and sensory recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Electro-acupuncture represents another method with minimal tissue damage and known to produce anti-hyperalgesia in animal models of inflammatory pain. Electro-acupuncture was also shown to improve motor recovery by assessing muscle electrical activity elicited under peripheral nerve stimulation [10]. However, no studies have explored its effects on peripheral nerve regeneration by measuring both motor and sensory recovery.…”
Section: Introductionmentioning
confidence: 99%
“…4 Several investigators have reported that a low-frequency electrical stimulation is a promise approach to accelerate nerve regeneration after injury. 5,6 However, a high frequency of electrical stimulation may increase failure of nerve regeneration. 7 Therefore, we conclude that the electrical stimulation can have a positive and negative impact on peripheral nerve regeneration simultaneously.…”
mentioning
confidence: 99%
“…13 14 In the present study we applied EA stimulation to the ruptured tendon with the expectation that the stimulation would have similar effects to those seen in our previous studies. [4][5][6][7] For the electrical stimulation, two acupuncture needles, acting as electrodes delivering a direct electric current, were in contact with the injured part of the tendon. However, because of the extremely small distance between the two electrodes, it is not clear whether the promotion Figure 3 Maximum breaking strength (as measured by tension testing) and cross-sectional area of the Achilles tendon of rats (n=10 per group) 10 days following tendon rupture.…”
Section: Discussionmentioning
confidence: 99%